An aetiological classification of birth defects for epidemiological research. Issue 1 (5th January 2005) - Wellesley, D; Boyd, P; Dolk, H; Pattenden, S
Abstract : Background: Congenital anomaly registers collect data on antenatally and postnatally detected anomalies for surveillance, research, and public health purposes. Each anomaly is coded using the International Statistical Classification of Diseases and Related Health Problems (ICD-9/ICD-10) based on body systems, allowing accurate comparisons between registers for individual anomalies. When commencing an environmental, epidemiological study, it became clear to us that there is no standard classification that takes aetiology into account. This paper describes a new classification for use in studies addressing aetiology. Method: A classification system was evolved and piloted using cases in a study of geographical variation in congenital anomaly prevalence.1 Cases that were difficult to categorise were noted, and after discussion with a team of experts, the classification was adjusted accordingly. Results and conclusion: A robust, hierarchical method of classifying birth defects into eight categories has been produced, for use at source of data registration in conjunction with, but independent of, ICD coding.